IMPLEMENTATION OF GEOL TEGALAN DANCE AS AN EFFORT TO IMPROVE PHYSICAL ABILITIES AND PRESERVE LOCAL CULTURE FOR ELEMENTARY SCHOOL STUDENTS - Ratnaningrum, Ika; Jazuli, M; Raharjo, Tri Joko; Widodo, Widodo; Ningrum, Alya Putri Maradika (Universitas Labuhanbatu, 2025)
Purpose – The Geol Tegalan Dance is a dance that is a characteristic as well as an icon of Tegal City, so the local government of Tegal City appeals to every level of education to teach this dance. The problems that arise in the field are primarily at the basic education level, especially in the lower classes, whose physical condition remains unstable. This means the Geol Tegalan Dance is only taught to high-grade students. In this study, the implementation of Geol Tegalan Dance learning in art learning at SD Negeri Randugunting 5, Tegal City, will be discussed.Methodology – This study uses a qualitative approach with an analytical descriptive design. Data was collected through observation, interviews, and documentation.Findings – The study's findings indicate that the implementation of Geol Tegalan Dance learning at SD Negeri Randugunting 5 in Tegal City progressed through the planning, implementation, and evaluation stages. However, in the implementation of teaching, several obstacles arise with multiple causative factors. The obstacles faced encompass seven aspects, each caused by factors including government policies, curriculum, teachers, and students. With the existing obstacles, researchers strive to provide solutions to overcome them. The solutions provided vary according to the aspects of obstacles faced.Contribution – This research will contribute to the evaluation of dance learning in elementary schools, especially in Geol Tegalan Dance. In addition, this research can introduce Tegal's regional identity, namely Geol Tegalan Dance.